Nuclear Structure Calculations for Two-Neutrino Double-β Decay - P. Sarriguren; O. Moreno; E. Moya de Guerra (Advances in High Energy Physics)
We study the two-neutrino double-β decay in 76Ge, 116Cd, 128Te, 130Te, and 150Nd, as well as the two Gamow-Teller branches that connect the double-β decay partners with the states in the intermediate nuclei. We use a theoretical microscopic approach based on a deformed self-consistent mean field with Skyrme interactions including pairing and spin-isospin residual forces, which are treated in a proton-neutron quasiparticle random-phase approximation. We compare our results for Gamow-Teller strength distributions with experimental information obtained from charge-exchange reactions. We also compare our results for the two-neutrino double-β decay nuclear matrix elements with those extracted from the measured half-lives. Both single-state and low-lying-state dominance hypotheses are analyzed theoretically and experimentally making use of recent data from charge-exchange reactions and β decay of the intermediate nuclei.